Global prevalence of natural disaster-induced acute respiratory infections: A systematic review and meta-analysis of 290,380 participants - Daffa, Muhammad B.; Khansa, Firyal; Ghifari, Muhammad H.; Zaskia, Siti R.; Jung, Yoonju (Narra X, 2024)
Acute respiratory infections (ARI) can be caused by the occurrence of natural disasters such as earthquakes, volcanic eruptions, landslides, tsunamis, floods, and droughts. The aim of this study was to determine the global prevalence of acute respiratory infections during post-natural disasters across countries. A systematic review and meta-analysis were conducted in accordance with the PRISMA guidelines. Studies reporting acute respiratory infections prevalence in natural disaster-impacted areas were identified and screened from PubMed, Scopus, Crosreff, Scilit, and medRxiv as of March 16th, 2024. The meta-analysis was conducted using the Freeman-Tukey double arcsine transformation with a random-effects model. A total of 15 out of 2,052 studies, covering 290,380 subjects, were included in the meta-analysis. The pooled estimate of acute respiratory infection prevalence following natural disasters across multiple countries was 43.0% (95% confidence interval (CI): 31–55%; p-Het<0.01; I²=99.97%). No statistical significance was observed between subgroups, including population density (p=0.281), country income (p=0.583), and types of disasters (p=0.468), suggesting the indiscriminate nature of disaster-induced acute respiratory infections. The highest prevalence was observed in studies from 2015–2019, with a prevalence of 52% (95%CI: 32.7–72.2%; p-Het<0.001; I²=99.97%). In conclusion, the global prevalence of disaster-induced ARI is considered high, reaching 43%, highlighting the need for countermeasures to address these diseases during disasters.